Effects of preconditioning hamstring resistance exercises on repeated sprinting-induced muscle damage in female soccer players - Chen, C. H.; Chen, Y. S.; Wang, Y. T.; Tseng, W. C.; Ye, X. (Biology of Sport, 2018)
To examine whether adding preconditioning hamstring resistance exercises to a regular warm-up prior to a repeated sprinting exercise provides protection against the sprinting-induced muscle damage. Ten female soccer players (mean ± SD age: 21.3 ± 4.5yrs; height: 171.34 ± 8.29 cm; weight: 68.53 ± 11.27 kg) participated in this study. After the familiarization visit, the subjects completed three separate randomly sequenced experimental visits, during which three different warm-up interventions were performed before the muscle-damaging protocol (12 sets of 30-m maximal repeated sprints): 1. Regular running and static stretching (Control); 2. Control with hyperextensions (HE); 3. Control with single leg Romanian deadlift (SLRD). Before (Pre), immediately (Post0), 24 hours (24hr), and 48 hours after (48hr) the sprints, hamstring muscle thickness, muscle stiffness, knee flexion eccentric peak torque, knee extension concentric peak torque, and functional hamstring to quadriceps ratios were measured. Repeated sprints have induced muscle damage (e.g., an average of 42% knee flexion eccentric strength reduction) in all three conditions. After the SLRD, hamstring muscle thickness decreased from 24hr to 48hr (p < 0.001). Additionally, muscle stiffness and eccentric strength for the SLRD showed no difference from baseline at 24hr and 48hr, respectively. When compared with the SLRD at 48hr, the muscle stiffness and the eccentric strength were greater and lower, respectively, in other protocols. The SLRD protocol had protective effect on sprinting-induced muscle damage markers than other protocols. Athletes whose competitions/training are densely scheduled may take advantage of this strategy to facilitate muscle recovery.